Upaya Pendidikan Karakter Siswa melalui Pembelajaran Bahasa Jawa - Utami, Sri; Wardani, Dimas Singgih Sulistyo (FKIP Universitas Wisnuwardhana, 2020)
Javanese language learning in schools starting at the Elementary School, Junior High School, and Senior High School / District School level is an equal local content that must be given, as an effort to form the character of students. Therefore in the National Education System Law No. 20 of 2003 article 3 which states that in fact in the world of National Education the function is to develop capabilities and shape the character and civilization of the nation in order to educate the life of the nation, and have a goal0 for students or society to have a behavior that is in accordance with Indonesian civilization and the development of the potential of students to become people of faith and piety always to God Almighty, noble, healthy, knowledgeable, capable, independent creative so that they can become democratic and responsible citizens. Therefore, the same is true if the East Java Governor's Regulation concerning the implementation of learning Javanese as a compulsory local content in East Java Province. Language which is a tool for communicating according to laws and regulations should be like the school intansi must implement learning0 Javanese. Javanese0 Javanese0 Javanese functioning0communicative and0 rolein0 as a means of introducing noble values, and politeness of courtesy by recognizing boundaries of Java.0 and languages ​​of Java functioning as communicative languages ​​and Javanese language (Javanese language). ngoko (rough), which furthermore the karma and ngoko records are divided into: 01) Javanese language karma innocent karma alus, 02) Javanese language ngoko innocent ngoko alus. In the era of globalization the existence of the use of Javanese language is now increasingly fading, not only in daily interactions, but also adding to educational institutions, one of which is in junior high school. The application of the Javanese language in the form of education intensity especially in middle school can certainly add and illustrate the values ​​of the politeness of students to those who communicate with students. One day implementation in one week using Javanese karma and the use of simple media such as posters and bells as a tool for alternating hours whose content uses Javanese language is expected to be one of the effective ways to shape characters in junior high school students.